Knowledge, attitude, practice and perception about menstruation and menstrual hygiene among adolescent school girls in rural areas of Raigad district - Parle, Jyoti; Khatoon, Zoya (International Journal Of Community Medicine And Public Health, 2019)
Background: Menstrual hygiene is essential to decrease susceptibility of urinary and reproductive tract infection and promotes better health of women. Cultural and religious beliefs concerning menstruation such as food taboos and untouchability have harmful impact on dignity and wellbeing of adolescent girls. As a consequence many girls lack appropriate and satisfactory information regarding menstruation and menstrual hygiene. Thereby it is crucial to assess knowledge, attitude, practice and perception about menstruation and menstrual hygiene. Methods: It was a cross-sectional study, conducted among 600 adolescent school girls in rural areas of Raigad district to assess knowledge, attitude, practice and perception about menstruation and menstrual hygiene via self made questionnaire. The data collected was analyzed using SPSS version 24. Chi square test was applied to find association between variables. Results: Overall more than half 53.3% and 52.8% of the respondent had poor knowledge and poor practice on menstruation and menstrual hygiene respectively. Despite of poor knowledge majority of respondent 55.2% heard about menstruation before attaining menarche. Factors that were significantly associated with knowledge of menstruation and menstrual hygiene were adolescent age (Χ2=267.294, p=0.00), mother’s education (Χ2=77.331, p=0.00) and practice on menstruation (Χ2=111.745, p=0.00). Conclusions: Health education strategies and awareness programme on menstruation and menstrual hygiene should be framed to promote better health of adolescent girl.